Portuguese Soap Operas: A Genre at the Crossroads - Manuel José Damásio; Jorge Paixão da Costa (International Journal of Film and Media Arts, 2019)
In the context of ever greater circulation of televisual content of all genres and formats, this paper focuses on the intersections between the global and the local to understand how a specific genre – soap opera – was localised in a specific cultural and geographical setting giving origin to a production model that gained local prominence and nowadays faces a number of new challenges. Our general argument draws on the empirical findings of original research on the molding of this specific televisual genre and format called “telenovela”, and the specific production mode associated with it, and reflects on its historical emergence and the contingencies of such a process. Our goal is to identify the variables that allowed this genre to gain local dominance and later achieve international circulation. Following the results of quantitative and qualitative research, we argue that the structure of the local production and distribution settings and the dominant ideology of the associated production culture promoted the emergence of original local production culture and sustains it until today.